Congenital Brachial Arteriovenous Fistula. Issue 4 (December 2016) - White, Dalila; Badgett, Mark; Petty, John K.; Garg, Nitin
Despite complex embryologic development, congenital large- and medium-sized arteriovenous (AV) communications are rare. The prevalence of congenital large- and medium-sized AV malformations (AVMs) has been estimated to be 0.08–1%. Malformations do not always result in arterial venous communications though, and could potentially involve single type of vessel (artery or vein or lymphatic). Nontraumatic congenital AV communication in medium/large vessel has been previously reported in a single case report only. In our certified vascular laboratory at a large academic medical center (>1, 000 studies per month), there have been no prior cases of medium to large vessel congenital AV communication. Although the etiology is unknown, this maldevelopment results in pathologic connections between arteries and veins upstream of the capillary bed. The most common site of AVMs are the head and neck (>50%), followed by the extremities, then the pelvis and visceral organs. Depending on the size, location, extent, and severity of the AVM, its clinical presentation can be highly variable, ranging from asymptomatic or anemia (usually with visceral AVMs and occult bleeding) to pain, edema, audible bruits, or neurosensory deficits and tissue loss in more severe cases. We present a case of brachial artery to brachial vein communication in a child. This would be the first reported case of this abnormality in a child. The importance of duplex ultrasound in diagnosis and management is discussed.